Clinical and laboratory characteristics of unintentional carbon monoxide poisoning due to coal stove in children. (2nd January 2017) - Bicilioglu, Yuksel; Anil, Murat; Yilmaz, Ismail; Bal, Alkan; Gokalp, Gamze; Kamit Can, Fulya; Zengin, Neslihan; Durak, Fatih; Anil, Ayse Berna
Abstract: To describe predictors for severe carbon monoxide (CO) poisoning in children due to coal stove. Patients ( n = 176) were divided into two groups retrospectively: severe and mild-moderate clinical presentation. Forty-two patients received hyperbaric oxygen (HBO) therapy. No patient died. pH < 7.30 ( p = 0.030; OR:1.0211), carboxyhemoglobin (COHb) ( p = 0.002; OR:1.0558), and mean platelet volume (MPV) ( p = 0.004; OR:1.4695) were significantly different between the groups. COHb > 20%, (AUC: 0.691) was comparable to those for pH (AUC: 0.536) and MPV (AUC: 0.639) ( p > 0.05) in ROC analysis. Although COHb, pH and MPV were poor predictors for severe manifestations, performance of MPV was similar to the COHb and pH levels.